Electrical, magnetic and structural properties of polymer-blended lanthanum-added nickel nano-ferrites. Issue 17 (1st December 2018) - Lenin, N.; Sakthipandi, K.; Rajesh Kanna, R.; Rajkumar, G.
Abstract: Polyvinyl alcohol (PVA)-blended NiLa x Fe2- x O4 ( x = 0.01, 0.03, 0.05, 0.07 and 0.09) nano-ferrites were investigated through characterization studies such as powder X-ray diffraction (XRD) pattern, vibrating sample magnetometer graph, field emission scanning electron microscope (FESEM) images, and electrochemical impedance spectra. XRD pattern showed the presence of spinel cubic structure. A spherical-like morphology of PVA-blended nano-ferrites was identified from FESEM images and it was confirmed that the particle size of PVA-blended NiLa x Fe2- x O4 nano-ferrites was approximately 35 nm. An increase in dielectric constant and a decrease in loss tangent as a function of La 3+ ions were noted in prepared nano-ferrites. Impedance analysis of PVA-blended NiLa x Fe2- x O4 nano-ferrites indicated resistive behavior. PVA-blended NiLa x Fe2- x O4 nano-ferrites showed a soft ferromagnetic nature. Further, saturation magnetization of PVA-blended NiLa x Fe2- x O4 nano-ferrites decreased while increases the content of La 3+ ions.